PENGARUH SEKTOR PARIWISATA TERHADAP KEMISKINAN DAN PENYERAPAN TENAGA KERJA DI SEMBALUN LOMBOK TIMUR PADA MASA COVID-19 - Rapii, Muhammad Rapii (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of: 1) the tourism sector on poverty during the Covid-19 period. 2) The tourism sector to absorb labor during the Covid-19 period. The research method used is quantitative research. While the type used is associative research method which aims to determine the influence or relationship between two or more variables. The collection of data and information in this study used secondary data with a data collection method, namely time series (time series) over a period of three years 2018-2020. The results of this study indicate that there is a positive and significant influence between the tourism sector on poverty and the contribution of the influence given is 41.2%. This study also shows a positive and significant influence between the tourism sectors on employment with the contribution of the influence given that is equal to 82.7%. Meanwhile, based on the individual parameter significance test, it was obtained t count (3.711) > t table (2.132) on the Poverty variable, which means H0 was rejected and H1 was accepted, while in the Labor Absorption variable obtained t count (4.373) > t table (2.132), then H0 rejected and H1 accepted. So the conclusion in this study is that tourism has a significant effect on poverty and employment.